New Algorithm for Conservative Treatment of Patients with Keratoconus - E. S. Milyudin; O. Yu. Smorodinova; K. E. Kuchuk (Oftalʹmologiâ)
The purpose of our study was to substantiate and evaluate the effectiveness of the conservative method of treating keratoconus in the early stages of the development of the disease. Patients and methods. The study of the effectiveness of the proposed method for the conservative treatment of keratoconus was performed on clinical material obtained by monitoring 39 patients (75 eyes) with a diagnosis of keratoconus stage I–III for at least 10 years. Every 4–6 months, all patients underwent an ophthalmological examination — visometry, autorefractometry, keratometry, keratotopography, pachymetry, biomicroscopy. Along with the study of the ophthalmic status of the patients, cardiointervalography was performed before starting conservative treatment. The assessment of vegetative homeostasis was performed using the Mustang-Diagnost device of the Technika company (Russia). Results. All patients observed by us were matched with corneal or corneoscleral gas-permeable contact lenses of various models and manufacturers. According to cardiointervalography, in 97 % of our patients vegetative dysfunction was determined, while in 85 % and all examined, a significant predominance of sympatheticotonic neurotrophic regulatory processes was determined. At the first stage of the conservative treatment of keratoconus pharmacological agents were selected. They potentiate cholinergic neurotrophic regulatory effects and activate aerobic processes in the tissues of the eyeball. The next step was the potentiation of sympathicotonic (ergotropic) neurotrophic regulatory processes. Treatment was carried out during the entire observation period, alternating complexes of preparations for 60 days. An increase in diopter strength along the steep meridian was noted in patients with keratoconus of all stages. In the group of patients with stage I keratoconus in 4 eyes out of 16, in patients with stage II disease in 7 eyes out of 35, in stage III patients in 7 eyes out of 24. Opposite, a study of the KISA % index in all observed patients showed a decrease in the coefficient values. Conclusions. The combination of therapeutic factors into tonic (trophotropic, anabolic) and phase (ergotropic, catabolic) regulatory blocks, taking into account their mutual neurodynamic synergism and in accordance with the phase nature of biorhythmogenesis of reparative processes, makes it possible to prevent the progression of keratoconus. The use of the treatment complex developed by us, which includes therapeutic treatment and correction with rigid gas-permeable contact lenses, corrects metabolic disorders and stabilizes collagen synthesis, which makes it possible to lay off the surgical treatment of patients with keratoconus.